The countryside and its role in the development of food security - خيربك مياد فهيم; نبال الجوراني (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Inadequate rural infrastructure leads to the isolation of communities, impedes the development of the food chain, and contributes to the loss of food after harvest, and this is linked to poverty and poor nutrition, To achieve growth and improve rural livelihoods, adequate rural infrastructure must be provided, including good rural roads, and reliable electricity, marketing and warehousing facilities, and digital networks will also invest in human capacities, supporting rural people to take advantage of new opportunities in areas such as agricultural advisory services, financial services, business development services, health and education services. Infrastructure investments will create a positive cycle of economic development. To achieve the best and strategic return, and thus it will have a prominent role in addressing issues of food security and poverty that have a significant political impact on government expenditures. Two well-known points of view on the urban and rural division appeared with him since the industrial revolution in Europe, as well as the acceleration inherent in the process of urbanization, Social, the pro-civilization view is a progressive process and one of the main forces driving technological innovation and economic development And social and economic change (anti-Malthusian thought) ,* The presence of the countryside and its investments and small and micro rural projects involves an essential existential aspect based on food production and achieving abundance in this production in order to reach food security in both its plant and animal parts, and thus owning the existential decision of national societies.